A predictive study : carbon monoxide emission modeling at a signalized intersection - Wee, Freddy Liang Kho; Puong, Ling Law (School of Engineering, Taylor’s University, 2014)
CAL3QHC dispersion model was used to predict the present and future carbon monoxide (CO) levels at a busy signalized intersection. This study attempted to identify CO “hot-spots” at nearby areas of the intersection during typical A.M. and P.M. peak hours. The CO concentration “hot-spots” had been identified at 101 Commercial Park and the simulated maximum 1-hour Time-Weighted Average (1-h TWA) ground level CO concentrations of 18.3 ppm and 18.6 ppm had been observed during A.M. and P.M. peaks, respectively in year 2006. This study shows that there would be no significant increment in CO level for year 2014 although a substantial increase in the number of vehicles is assumed to affect CO levels. It was also found that CO levels would be well below the Malaysian Ambient Air Quality Guideline of 30 ppm (1-h TWA). Comparisons between the measured and simulated CO levels using quantitative data analysis technique and statistical methods indicated that CAL3QHC dispersion model correlated well with measured data.